Financing small and medium scale enterprises in Madina municipality: the case of GCB bank - Ansa-Akyea Eugene (knust, 2025)
A Thesis submitted to the Department of Accounting and Finance, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirement for the degree of MASTER OF SCIENCE (ACCOUNTING AND FINANCE)